Malignant astrocyte swelling and impaired glutamate clearance drive the expansion of injurious spreading depolarization foci. Issue 4 (April 2022) - Menyhárt, Ákos; Frank, Rita; Farkas, Attila E; Süle, Zoltán; Varga, Viktória É; Nyúl-Tóth, Ádám; Meiller, Anne; Ivánkovits-Kiss, Orsolya; Lemale, Coline L; Szabó, Írisz; Tóth, Réka; Zölei-Szénási, Dániel; et al.
Spreading depolarizations (SDs) indicate injury progression and predict worse clinical outcome in acute brain injury. We demonstrate in rodents that acute brain swelling upon cerebral ischemia impairs astroglial glutamate clearance and increases the tissue area invaded by SD. The cytotoxic extracellular glutamate accumulation (>15 µM) predisposes an extensive bulk of tissue (4–5 mm 2 ) for a yet undescribed simultaneous depolarization (SiD). We confirm in rat brain slices exposed to osmotic stress that SiD is the pathological expansion of prior punctual SD foci (0.5–1 mm 2 ), is associated with astrocyte swelling, and triggers oncotic neuron death. The blockade of astrocytic aquaporin-4 channels and Na + /K + /Cl − co-transporters, or volume-regulated anion channels mitigated slice edema, extracellular glutamate accumulation (<10 µM) and SiD occurrence. Reversal of slice swelling by hyperosmotic mannitol counteracted glutamate accumulation and prevented SiD. In contrast, inhibition of glial metabolism or inhibition of astrocyte glutamate transporters reproduced the SiD phenotype. Finally, we show in the rodent water intoxication model of cytotoxic edema that astrocyte swelling and altered astrocyte calcium waves are central in the evolution of SiD. We discuss our results in the light of evidence for SiD in the human cortex. Our results emphasize the need of preventive osmotherapy in acute brain injury.